The Implementation of Educational Facilities and Infrastructure Management in Supporting Learning Process during Pandemic Covid-19 (Study at SMA Plus As-Salaam Bandung) - Erwin Muslimin; Hisny Fajrussalam; Muhibbin Syah; Mohamad Erihadiana (CV. Creative Tugu Pena, 2021)
Talking about the world of education was certainly not be separated from the facilities and infrastructure that available in schools. So, it can be achieve an optimal and maximum learning process. Educational facilities and infrastructure in a school are very supportive of the development and construction of a superior and quality educational institution. In today's modern era, all educational institutions are competing to complement existing educational facilities and infrastructure in order to support a good and optimal learning process, especially during pandemic Covid-19. Educational institutions or schools as much as possible provide good and quality learning supported by educational facilities or facilities and infrastructure to support learning during the Covid-19 pandemic without reducing the quality of the learning process itself.. This research aims to determine the extent of management of educational facilities or facilities and infrastructure in supporting the learning process during the Covis-19 pandemic at SMA Plus As-Salaam Bandung. This research was conducted by means of interviews or observations about the implementation of educational facility management in supporting the learning process at SMA Plus As-Salaam which is located at the Cibaduyut canal road, Dayeuh Kolot sub-district, Bandung Regency, West Java. Keywords: Supporting Learning Process, Learning of Pandemic Covid-19, Management Education